An address configuration protocol for 6LoWPAN wireless sensor networks based on PDAD - Wang, Xiaonan; Yang, Yuan; Yao, Yufeng; Cheng, Hongbin (Computer standards and interfaces, 2014)
In a wireless sensor network (WSN), data collected by a sensor node need to be associated with location information in order to support real-world applications. Taking the WSN characteristics into account, this paper proposes an address configuration scheme based on location information and passive duplicate address detection (PDAD). In this scheme, the network architecture based on location information is presented, and based on this architecture the address initialization algorithm and address maintenance algorithm are proposed. The address initialization algorithm is performed once the network starts, and it is made up of the initialization address configuration sub-algorithm (IAC) and the initialization location PDAD sub-algorithm (ILPDAD). The address maintenance algorithm is performed after the initialization algorithm is complete, and it is composed of the maintenance address configuration sub-algorithm (MAC) and the maintenance location PDAD sub-algorithm (MLPDAD). During the address initialization process (address maintenance process), a new node first uses IAC (MAC) to obtain an address and then performs ILPDAD (MLPDAD) to ensure the address uniqueness. Since beacon frames are employed to achieve IAC (MAC) and ILPDAD (MLPDAD), the address configuration cost and delay are reduced. Moreover, IAC (MAC) is based on location information and ILPDAD (MLPDAD) is based on PDAD, so there are always the sufficient address resources for address configuration without address reclamation. In this way, the extra cost and delay caused by both the address reclamation and the address configuration failure are avoided. This paper evaluates the performance of this scheme, and the data results show that this scheme effectively reduces the address configuration delay and cost. •The network architecture based on location information is proposed.•Based on this architecture, the address initialization algorithm is proposed.•Based on this architecture, the address maintenance algorithm is proposed.